A discourse on the method of correctly conducting one's reason and seeking truth in the sciences - Descartes, René (Oxford world's classics (Oxford University Press), 2006)
'I concluded that I was a substance whose whole essence or nature resides only in thinking, and which, in order to exist, has no need of place and is not dependent on any material thing.'